Efektivitas Implementasi Model Pembelajaran SMK dalam Memenuhi Tantangan Revolusi Industri 4.0 - Sunarto Sunarto; Didi Supriadi (Universitas Sarjanawiyata Tamansiswa, 2019)
Abstracts. The study aimed to determine whether the learning model used in vocational schools has been effective in producing graduates who are independent, competitive, and can be absorbed by domestic and foreign industries. This research is a quantitative descriptive. This type of research is evaluation research. The evaluation consists of inputs, contexts, processes, products and outcomes (CIPPO). The research conducted at vocational school in Yogyakarta Special Region and Central Java Province. The research sample was taken using purposive sampling. The majority of learning models applied in vocational schools, both theory and practice, are problem-based learning models and work-based learning models. The impact of the implementation of the learning model on the quality of graduates is that an average of 40% of graduates have worked according to expertise, of which 41% are work in the domestic industry. Most vocational schools have utilized the cooperation network in managing the vocational school. Only about 47% use digital industrial network 4.0. Collaboration with utilizing domestic digital industry 4.0 as much as 50% and abroad as much as 38.3%. Policy solutions and practical implementation to increase the absorption of vocational graduates, namely: improving learning facilities, industry-based curriculum, routinely holding job matching, job fairs, alumni networks, collaboration with the ministry of industry, the ministry of labor.